A Pathway for Esophageal Obstruction is Associated with Decreased Cost and Length-of-Stay. Issue 2 (June 2022) - Klutts, Garrett N.; Tingquist, Nicholas D.; Pagteilan, John; Muesse, Jason L.; Sexton, Kevin W.; Marino, Katy; Steliga, Matthew A.
Malignancy of the esophagus or mediastinum can present with obstruction. Our focus is to identify the most effective means of managing this population. Data was gathered from a single institution for patients admitted with esophageal obstruction. Patients were categorized based on admission to thoracic surgery or the hospitalist service. Primary end-points were hospital length-of-stay (LOS) and hospital cost. The mean LOS was 4.4 days when admitted to thoracic surgery versus 13.5 days when admitted to a hospitalist ( P  = .0005). The mean overall cost was $43, 902 less per patient when admitted to thoracic surgery ($75 809 vs $31 907; P  = .003).